Human milk-derived versus bovine milk-derived fortifier use in very low birth weight infants: growth and vitamin D status - Lavassani, Emmanuelle; Tauber, Kate A.; Cerone, Jennifer B.; Ludke, Jennifer; Munshi, Upender K. (Frontiers in Pediatrics, 2024)
Human milk derived fortifier (HMDF) used with human milk feeding in extremely premature infants reduces adverse outcome risks of early exposure of bovine milk ingredients but may not provide enough nutrients for adequate catch-up growth as provided by bovine milk derived fortifier (BMDF) Objective To compare HMDF and BMDF effects on growth parameters and serum 25-hydroxy vitamin D (25OHD) levels in preterm very low birth weight (VLBW) infants during first 8 weeks of life.Methods Retrospective chart review of inpatient VLBW infants with birth weight <1500g and gestational age < 32 completed weeks who received either their mother's milk or donor breast human milk fortified with HMDF or BMDF for first 8 weeks. Weight, head circumference and length gain were calculated at 4-and 8-weeks of age along with 25OHD level.Results A total of 139 VLBW infants (91 HMDF + 48 BMDF) received fortified human milk without any supplemental premature formula from birth to 4-weeks and 44 (37 HMDF + 7 BMDF) of those continued until 8-weeks of age. There was no statistically significant difference in the growth parameters between the two groups at 4-and 8-weeks of age. Serum 25OHD level in the HMDF group was significantly higher compared to the BMDF group at 4-weeks of age despite receiving lower vitamin D supplementation.Similar gain in growth parameters in HMDF and BMDF groups at 4-and 8-weeks of age suggest that HMDF provides adequate nutrients for growth in VLBW infants. Higher 25OHD level in HMDF may suggest better absorption.